2012
DOI: 10.1177/1040638712442879
|View full text |Cite
|
Sign up to set email alerts
|

Lipid emboli in a Vietnamese potbellied pig (Sus scrofa)

Abstract: A 2-year-old, spayed female Vietnamese potbellied pig (Sus scrofa) with a body condition score of 6 out of 6 and a weight of approximately 113 kg presented for polyuria and polydipsia. There was mild abdominal distention, and the abdomen felt very firm on palpation. The owner also reported lethargy and hyporexia of several weeks' duration. On presentation, the pig could ambulate normally; body temperature, respiratory rate, and heart rate were within normal limits. The pig was sedated to facilitate thorough ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…In addition, similar macroscopic and histopathological findings have been observed in the pet Vietnamese potbellied pig. 15 These observations confirm the fact that the condition is not directly caused by the given treatments, although there was a predominance of unscheduled deaths in the treated groups. The condition, however, seems to be related to prolonged periods of reduced food intake together with the presence of lipogranulomatous inflammation in the retroperitoneal and/or visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, similar macroscopic and histopathological findings have been observed in the pet Vietnamese potbellied pig. 15 These observations confirm the fact that the condition is not directly caused by the given treatments, although there was a predominance of unscheduled deaths in the treated groups. The condition, however, seems to be related to prolonged periods of reduced food intake together with the presence of lipogranulomatous inflammation in the retroperitoneal and/or visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 72%
“…Very similar macroscopic and histopathological changes in form of lipid embolism in lung and kidney as well as lipogranulomatous inflammation in retroperitoneal/visceral adipose tissue have previously been observed in one pet Vietnamese potbellied pig. 15 Recently, Renner et al also described lipogranulomatous inflammation in retroperitoneal and/or visceral adipose tissue in several obese high-fat diet fed GM, 16 with no involvement of SC adipose tissue. These authors observed lipid in the lungs of the animals as well; however, in contrast to the present study, it was detected within the lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3 possible explanations were given for the release of adipose tissue into the blood vessels of that pig: the presence of abdominal fat necrosis, hepatic lipidosis, and the surgical procedures performed (exploratory celiotomy, CT-guided collection of a bone marrow aspirate sample, and percutaneous hepatic biopsy). 16 In the potbellied pig of the present report, signs of trauma were not identified during necropsy; it had not undergone any surgical procedures during the preceding months. Hepatic lipidosis and pancreatic necrosis were ruled out on the basis of the absence of pathological lesions in the liver and pancreas and the adipose tissue surrounding both of them.…”
Section: Commentsmentioning
confidence: 61%
“…To our knowledge, there is just 1 other report 16 of lipid emboli in a Vietnamese potbellied pig. In that pig, intravascular fat droplets were detected by means of an indirect method based on anti-fibrinogen immunohistochemical analysis, but the cause of the fat emboli remained unclear.…”
Section: Commentsmentioning
confidence: 99%
“…Применяют методы выявления ЖЭ путем посмерт-ной компьютерной томографии с ангиографией (или без нее) и биопсии длинной иглой [41] с последующим под-тверждением их результатов при вскрытии. Считается, что при формировании жирового эмбола его поверхность покрывается тромбоцитами, элементами клеток крови, фибрином; липиды при парафиновой проводке исчезают, но адсорбированный фибриноген вокруг липидных ка-пель остается в целости [42]. Исходя из этого, ЖЭ в пара-финовых срезах косвенно можно подтвердить иммуноги-стохимически (антитела к фибриногену и CD61) обнару-жением фибриногена и тромбоцитов в области оптически пустых пространств в кровеносных сосудах.…”
unclassified